2009
DOI: 10.2152/jmi.56.42
|View full text |Cite
|
Sign up to set email alerts
|

Awa (Tokushima) lactate-fermented tea as well as green tea enhance the effect of diet restriction on obesity in rats

Abstract: Drinking tea is recommended for promoting health due to its bioactive nutrients, such as catechins and caffeine. In Tokushima area, we have a unique traditional tea, named Awa tea, which are fermented with Lactobacillus pentosus and Lactobacillus plantarum. The present study was designed to investigate anti-obesity effects of the Awa tea and compare with those of non-fermented green tea. Obese male Wistar rats (19 weeks of age) were given by low energy diets containing 3% of Awa and green tea extracts, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…193 Administration of green tea extract (3% of diet) to rats fed a high fat diet decreased body weight gain and visceral fat accumulation, this correlated with an increase in fecal lipids. 194 An open study carried out in moderately obese patients showed that administration of AR25 for 3 months decreased body weight and waist circumference by 4.6% and 4.48% respectively. 195 Again, these effects could be the result of the aforementioned combination of enzyme inhibition and increased thermogenesis.…”
Section: Green Teamentioning
confidence: 98%
“…193 Administration of green tea extract (3% of diet) to rats fed a high fat diet decreased body weight gain and visceral fat accumulation, this correlated with an increase in fecal lipids. 194 An open study carried out in moderately obese patients showed that administration of AR25 for 3 months decreased body weight and waist circumference by 4.6% and 4.48% respectively. 195 Again, these effects could be the result of the aforementioned combination of enzyme inhibition and increased thermogenesis.…”
Section: Green Teamentioning
confidence: 98%
“…Recent studies have reported that oral feeding 1.5% and 4% green, oolong, black, and pu-erh tea leaves to SD rats for 30 weeks could lower the serum concentrations of total cholesterol and lipoprotein cholesterol levels (10). Our previous study also demonstrated that compared to a low-energy diet, oral ingestion of 3.0% Awa-bancha leaves combined with a low-energy diet significantly reduced body weight and prevented fat absorption in obese rats (11). It is very encouraging to find that Goishi tea leaves can further reduce body weight and fat mass during diet restriction.…”
Section: Introductionmentioning
confidence: 64%
“…A study performed in streptozotocin-induced diabetic rats showed that addition of green tea extracts to the diet (0.01% and 0.2% of diet) significantly reduced maltase (both doses) as well as saccharase and lactase (higher dose) activities 193. Administration of green tea extract (3% of diet) to rats fed a high fat diet decreased body weight gain and visceral fat accumulation, this correlated with an increase in fecal lipids 194. An open study carried out in moderately obese patients showed that administration of AR25 for 3 months decreased body weight and waist circumference by 4.6% and 4.48% respectively 195.…”
Section: Both Anti-lipase and Anti-amylase Activitymentioning
confidence: 99%